Altered Vaginal Microbiota Composition Correlates With Human Papillomavirus and Mucosal Immune Responses in Women With Symptomatic Cervical Ectopy - López-Filloy, Mariana; Cortez, Flor J.; Gheit, Tarik; Cruz y Cruz, Omar; Cruz-Talonia, Fernando; Chávez-Torres, Monserrat; Arteaga-Gómez, Cristina; Mancilla-Herrera, Ismael; Montesinos, Juan J.; Cortés-Morales, Víctor Adrián; Aguilar, Cecilia; Tommasino, Massimo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical ectopy is a benign condition of the lower genital tract that is frequently detected in women of reproductive age. Although cervical ectopy is regarded as a physiological condition, some women experience symptoms such as leucorrhoea, persistent bleeding and recurrent vaginal infections that require medical intervention. Cervical ectopy has not been linked to cervical cancer, but it is thought to facilitate the acquisition of sexually transmitted diseases (STDs), like Human Papillomavirus (HPV) infection, as it provides a favorable microenvironment for virus infection and dissemination. We and others have described the presence of oncogenic HPV types in women with symptomatic cervical ectopy. The relevance of this finding and the impact of symptomatic cervical ectopy on the cervicovaginal microenvironment (vaginal microbiota, immune and inflammatory responses) are currently unknown. To shed some light into the interplay between HPV, the vaginal microbiota and mucosal immune and inflammatory responses in the context of this condition, we enrolled 156 women with symptomatic cervical ectopy and determined the presence of HPV using a type-specific multiplex genotyping assay. Overall, HPV was detected in 54.48% women, oncogenic HPV types were found in more than 90% of HPV-positive cases. The most prevalent HPV types were HPV16 (29.4%), HPV31 (21.17%) and HPV18 (15.29%). Next, we evaluated the vaginal microbial composition and diversity by 16S rDNA sequencing, and quantified levels of cytokines and chemokines by flow cytometry using bead-based multiplex assays in a sub-cohort of 63 women. IL-21 and CXCL9 were significantly upregulated in HPV-positive women (p=0.0002 and p=0.013, respectively). Women with symptomatic cervical ectopy and HPV infection had increased diversity (p<0.001), and their vaginal microbiota was enriched in bacterial vaginosis-associated anaerobes (Sneathia, Shuttleworthia, Prevotella, and Atopobium) and depleted in Lactobacillus spp. Furthermore, the vaginal microbiota of women with symptomatic cervical ectopy and HPV infection correlated with vaginal inflammation (IL-1β, rho=0.56, p=0.0004) and increased mucosal homeostatic response (IL-22, rho=0.60, p=0.0001). Taken together, our results suggest that HPV infection and dysbiotic vaginal communities could favor a vaginal microenvironment that might delay the recovery of the cervical epithelium in women with symptomatic cervical ectopy and favor STDs acquisition.